2018
DOI: 10.1101/497982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serotonin regulates mitochondrial biogenesis and function in rodent cortical neurons via the 5-HT2A receptor and SIRT1-PGC-1α axis

Abstract: Mitochondria in neurons in addition to their primary role in bioenergetics also contribute to specialized functions including regulation of synaptic transmission, Ca 2+ homeostasis, neuronal excitability and stress adaptation. However, the factors that influence mitochondrial biogenesis and function in neurons remain poorly elucidated. Here, we identify an important role for serotonin (5-HT) as a regulator of mitochondrial biogenesis and function in rodent cortical neurons, via a 5-HT 2A receptor-mediated recr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Serotonin coevolved with mitochondria, once free-living endosymbiotic organelles that generate most of the chemical energy that fuels the cell's biochemical reactions (Picard, McEwen, Epel, & Sandi, 2018). Serotonin (like the other biogenic amines dopamine and norepinephrine) is a very ancient neurotransmitter with cell bodies buried deep in the brain stem (it has been around a long time in evolutionary terms) and plays a key role in mitochondrial biogenesis (Fanibunda et al, 2019).…”
Section: Depression As An Evolved Adaptationmentioning
confidence: 99%
“…Serotonin coevolved with mitochondria, once free-living endosymbiotic organelles that generate most of the chemical energy that fuels the cell's biochemical reactions (Picard, McEwen, Epel, & Sandi, 2018). Serotonin (like the other biogenic amines dopamine and norepinephrine) is a very ancient neurotransmitter with cell bodies buried deep in the brain stem (it has been around a long time in evolutionary terms) and plays a key role in mitochondrial biogenesis (Fanibunda et al, 2019).…”
Section: Depression As An Evolved Adaptationmentioning
confidence: 99%
“…Studies in rodent neurons have also shown that 5‐HT promotes the upregulation of Sirt 1 SIRT1; a NAD + ‐dependent deacetylase induces mitochondrial biogenesis involving PGC‐1α that regulates transcription of mitochondrial transcription factor A (TFAM), a gene required for mitochondrial biogenesis, the result of which is reflected in the altered levels of mtDNA. The study also showed that lower levels of 5‐HT affect the biogenesis of mitochondria by master regulators SIRT1 and PGC‐1α, respiratory capacity and OXPHOS efficiency and obviously decreases efficiency of ATP synthesis (Fanibunda et al, 2019). Such a chain of dysfunctional reactions can increase the susceptibility of migraine.…”
Section: Genetic Perspectives and Evidence Of Dysfunction From The Mi...mentioning
confidence: 99%
“…Furthermore, impaired mitochondrial biogenesis is evident in patients with AD and PD (Sheng et al, 2012; Thomas et al, 2012). Using a combination of selective antagonists and KO animals, Vaidya and co‐workers demonstrated that activation of 5‐HT 2A receptors promotes mitochondrial biogenesis and improves mitochondrial function, potentially improving the ability of neurons to buffer stress (Fanibunda et al, 2019). In cortical cultures, stimulation of 5‐HT 2A receptors with DOI protected neurons against both kainate‐ and H 2 O 2 ‐induced cell death (Fanibunda et al, 2019).…”
Section: Role Of 5‐ht2a Receptors In Mitochondrial Functionmentioning
confidence: 99%
“…Using a combination of selective antagonists and KO animals, Vaidya and co‐workers demonstrated that activation of 5‐HT 2A receptors promotes mitochondrial biogenesis and improves mitochondrial function, potentially improving the ability of neurons to buffer stress (Fanibunda et al, 2019). In cortical cultures, stimulation of 5‐HT 2A receptors with DOI protected neurons against both kainate‐ and H 2 O 2 ‐induced cell death (Fanibunda et al, 2019). Moreover, mitochondrial biogenesis was promoted by both the hallucinogenic 5‐HT 2A agonist DOI and the non‐hallucinogenic agonist lisuride (Fanibunda et al, 2019).…”
Section: Role Of 5‐ht2a Receptors In Mitochondrial Functionmentioning
confidence: 99%
See 1 more Smart Citation